EFFECTS OF TRADE LIBERALIZATION POLICIES IMPLEMENTED IN 1980-2018 PERIOD ON TURKEY'S ECONOMIC PERFORMANCE - ULUBEYOĞLU, Burak Furkan; DURAN, Tarık; ÇIMAT, Ali (Atlas Journal, 2021)
The liberalization of trade in world economies or the restriction of trade with interventionist approaches are discussed from past to present. Throughout history, in economies, the aim was freedom of trade, while in reality, interventionist approaches have been mentioned. Today, the concept of liberalism has been replaced by globalization. In this study, firstly, the studies dealing with the relationship between trade liberalization and economic growth of developed; developing and less developed countries are examined. In some East Asian countries, it is seen that there is increase in exports and a positive relationship between trade freedom and growth. However, in some African and Latin American countries this has not happened. Trade liberalization policies and economic packages and programs in Turkey have been gaining momentum since 1980. The aim of this study is to examine the direction of the relationship between trade liberalization and economic growth in Turkey. The study obtained an index expressing trade liberalization using GDP, import and export data. As a result of the study, it was determined that the relationship between trade liberalization and foreign trade volume in Turkey is in a positive direction.